Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1074/jbc.m110.216184
|View full text |Cite
|
Sign up to set email alerts
|

Transportin 2 Regulates Apoptosis through the RNA-binding Protein HuR

Abstract: In response to severe stress, apoptotic cell death is engaged. Apoptosis is a well orchestrated process that involves the activation and implication of many factors. In this study, we identified a role for the nuclear trafficking factor TRN2 (transportin 2) in cell death. TRN2 is normally responsible for the nuclear import of the RNA-binding protein HuR. During apoptosis, however, HuR accumulates in the cytoplasm. This is due to the caspase-mediated cleavage of the cytoplasmic fraction of HuR. One of the cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…25 HuR-CP1 causes a similar effect in response to lethal stress, by binding to the import factor transportin-2 and augmenting cytoplasmic localization of HuR. 41 Here we show that together the two CPs are capable of stabilizing caspase-9 mRNA, even to a greater extent than wtHuR, and our previous data also indicate that the two CPs of HuR are most potent for inducing apoptosis when present simultaneously. 24 Therefore, these data illustrate that the coordination between HuR and its CPs is an important aspect of the effects they have.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…25 HuR-CP1 causes a similar effect in response to lethal stress, by binding to the import factor transportin-2 and augmenting cytoplasmic localization of HuR. 41 Here we show that together the two CPs are capable of stabilizing caspase-9 mRNA, even to a greater extent than wtHuR, and our previous data also indicate that the two CPs of HuR are most potent for inducing apoptosis when present simultaneously. 24 Therefore, these data illustrate that the coordination between HuR and its CPs is an important aspect of the effects they have.…”
Section: Discussionsupporting
confidence: 51%
“…HuR shuttles between the nucleus and the cytoplasm, and while only a fraction of it (B10-20%) localizes to the cytoplasm, 36,37 it is in this compartment where HuR exercises its main biological effects. [15][16][17]30,[38][39][40] Our recent papers 18,24,25,41 strengthen this idea and show that the HuR-CPs, generated from B50% of cytoplasmic HuR, are both sufficient and necessary for HuR-mediated effects. 18 However, as not all cytoplasmic HuR is cleaved, wt HuR and both of its CPs are all present simultaneously, and thus may be affected by one another when exercising their effects.…”
Section: Discussionmentioning
confidence: 56%
“…Other ongoing work includes attempting to further understand the function of CP1 in cells and uncover the exact signal by which CP1 may provide feedback to HuR and DR5 mRNA. 32 Our data along with others show that HuR can assert its influence and be influenced at many points in this powerful apoptotic pathway. 13 Confirmatory studies in other tumor systems will determine if all cancer cells select for HuR's ability to modulate or put the brakes on DR5-directed signaling in an effort to avoid apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…3,13 The precise role and/or relevance of HuR cleavage (CP1) in this pathway is currently under investigation, although others have linked this event to pp32's induction of apoptosis. 23,31,32 Clinically, we have previously shown that cytoplasmic HuR levels in PDA specimens can be a useful predictive marker for gemcitabine therapy. 19,20 Based on our current results, the cytoplasmic HuR levels could also be a predictive marker for DR5-targeted therapy, given the inverse relationship between cytoplasmic HuR abundance and DR5 intensity in patient tumors (p < 0.0001, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Protein kinase C (PKC) and mitogen-activated protein kinase (MAPK) p38 also modulate the association of HuR with target mRNA [38][39][40]. Although HuR is predominantly nuclear, it is capable of shuttling to the cytoplasm through its nucleoyctoplasmic shuttling sequence (HNS) and transport machinery including chromosome region maintenance 1(CRM1), transportins 1 and 2, and importin-1α [41][42][43][44]. In addition, under stress conditions such as arsenite or heat shock, HuR aggregates in the cytoplasm with RNAs, known as RNA granules or stress granules, where mRNAs are stored or translationally suppressed [37,45].…”
Section: Hurmentioning
confidence: 99%